Localization of the occluded vessel in acute myocardial infarction - Rafla, Samir; Kamal, Amr (Journal of Cardiology and Cardiovascular Medicine, 2020)
This is a review of features in ECG to diagnose the culprit artery responsible for the infarction. Localization of the occluded vessel in acute myocardial infarction is important for many reasons: to know which artery is to dilate and stent; to assess the severity of the lesion; to compare with the echocardiographic area with hypokinesia or akinesia and to differentiate the recent from the old occluded vessel. The ST-segment changes in 12-lead ECG form the basis of diagnosis, management, and prognosis.